Robótica livre como alternativa didática para a aprendizagem de música - Antunes, Sabrina Favaretto (2016)
The present study aimed at exploring the potential of educational robotics as an aid to the teaching of music, with a view to finding alternatives that could minimize the lack of both musical instruments in schools and teachers without specific training to act in Music teaching. This demand was strengthened by the return of this component to the school curricula of Basic Education, through the approval of Law 11,769 / 2008. To deal with this theme, the concepts of learning, based on Juan Ignacio Pozo, and of musical learning, the implications of music in the development of the subject and the Orff method as a proposal of teaching of music, through dialogues between Gardner, Orff, Beyer and Gobbi. Other elements are related to public policies aimed at musical education in the Brazilian school context, in which informatics is presented as a learning resource, exploring free robotics as an alternative for music education. The field work was carried out by four children aged ten to twelve, all of them living in the municipality of Sertão, Rio Grande do Sul, and their methodology was developed based on an exploratory research, qualitative. The workshops had four stages and, during their execution, the moments of experimentation were documented and analyzed together with a questionnaire carried out after the workshop period. In order to verify the extent to which the robotic device constructed from this research can assist in the development of two auxiliary learning processes, worked by Pozo, the recovery and transfer process being the process of learning how to manage learning. Potential especially in relation to the process of consciousness, more specifically in relation to the evaluation category. Through demonstrations and interactions between the participants during the workshops, it is possible to perceive incidences in all categories of analysis proposed. With the study, it was found that it was possible to build a low-cost robotic device capable of implementing actions or processes that a teacher without specific training in Music might not be able to.